2016
DOI: 10.1111/sji.12416
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Polymeric Immunoglobulin Receptor and Neonatal Fc Receptor Expression in the Gut Mucosa of Immunodeficiency Virus‐Infected Rhesus Macaques

Abstract: Polymeric immunoglobulin receptors (pIgR) and neonatal Fc receptors (FcRn) are crucial immunoglobulin (Ig) receptors for the transcytosis of immunoglobulins, that is IgA, IgM and IgG, the levels of which in mucosal secretions were altered in both HIV-and SIV-infected individuals. To gain an insight into the changes of pIgR and FcRn expression after immunodeficiency virus (SHIV/SIV) infection, real-time RT-PCR methods were established and the mRNA levels of pIgR and FcRn in normal and SHIV/SIV-infected rhesus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…When the pathogen stimulates the mucosal epithelium, the expression of FcRn may be regulated. Simian/human immunodeficiency virus (SHIV) infection decreases FcRn and pIgR expression, which may also be the mechanism responsible for its pathogenesis in rhesus monkeys (Wang and Yang, 2016). On the other hand, TGEV up-regulates FcRn expression, which is potentially what provides the mucosal protection.…”
Section: Discussionmentioning
confidence: 99%
“…When the pathogen stimulates the mucosal epithelium, the expression of FcRn may be regulated. Simian/human immunodeficiency virus (SHIV) infection decreases FcRn and pIgR expression, which may also be the mechanism responsible for its pathogenesis in rhesus monkeys (Wang and Yang, 2016). On the other hand, TGEV up-regulates FcRn expression, which is potentially what provides the mucosal protection.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have found that IgG also plays an important role against pathogen infection in mucosal sites, while the neonatal Fc receptor (FcRn) is the only IgG transport receptor (Tsuruta et al, 2012). Down-regulation of FcRn and pIgR has been shown in the tracheal mucosa of SHIV/SIV-infected rhesus macaques (Wang and Yang, 2016; Li et al, 2017). Further, transmissible gastroenteritis virus infection up-regulates FcRn through TLR3 and RIG-I in porcine intestinal epithelial cells (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…For example, enterotoxigenic E. coli suppresses pIgR mRNA expression in vivo [ 118 ]. Similarly, simian immunodeficiency virus (SIV) and chimeric simian/human immunodeficiency virus (S/HIV) was able to downregulate pIgR mRNA expression in the gastrointestinal and respiratory mucosa of infected rhesus macaques [ 119 , 120 ], suggesting HIV may also use pIgR downregulation as an immune evasion tactic.…”
Section: Subversion Of the Pigr/sig System By Pathogensmentioning
confidence: 99%